The experiences of diploma registered nurses returning to undergraduate study in Qatar: A descriptive qualitative study. (August 2020) - MacDonald, Christine; Benjamin, Kathleen; Wolsey, Carolyn; Topping, Anne
Abstract: Background: Qatar aspires to provide world-class healthcare comparable with Western countries. Compelling evidence demonstrating the positive effects of bachelor of nursing (BN) educated nurses on patient outcomes is creating a global demand for these graduates, particularly in contexts such as Qatar where historically RN-to-BN programs were unavailable. Objective: The aim of this study was to examine the return to education experiences of diploma educated registered nurses (RNs) undertaking a bachelor program. Methods: This descriptive qualitative study included 19 diploma educated registered nurses enrolled in a BN program in a Qatar campus of a Canadian university. Focus groups and thematic analysis were used. Results: Three major themes described RNs' experiences of returning to education: the right time, balancing act and rewards. The convergence of timing, BN program availability and employer sponsorship were significant levers. Returning to education was challenging and required balancing competing demands of work, home, and study. The exposure to enquiry-based learning required rapid development of study skills to enable learning. Previous education was often seen as incongruent with requirements for academic success. A notable omission from accounts was reference to professional identity. Undertaking the program brought returns such as increased self-esteem, enhanced knowledge and potential for career progression. Organizational culture and commitment appeared to impact on students' experience. Conclusions: Completing a BN program was reward for the challenges engendered by returning to education. Effective partnerships and structural support between academic and service providers are required to ensure the benefits of BN attainment become embedded and impact on professional identity.